Outbreak investigation of viral exanthem in Jharkhand, India: an eye opener for surveillance managers and vaccine policy makers - Pall, Sahir; Kumar, Dewesh (International Journal Of Community Medicine And Public Health, 2018)
Background: Chicken pox outbreaks are frequent in tribal state of Jharkhand but rarely they are reported and investigated. Based on the preliminary information from field about the spurt of fever with rash cases in the inmates of a residential school, an outbreak investigation was undertaken to establish the disease outbreak and take appropriate steps of control and prevention of further transmission. Methods: The outbreak investigation using shoe-leather epidemiology was carried out in the month of March 2016 accordingly the standard steps of investigation in Chakulia block of Jharkhand, India and a fixed number of blood samples were sent to the apex medical institute of Jharkhand for its confirmation by laboratory tests. Concurrently control and preventive steps were taken to check further transmission of the viral exanthem. Results: A total of 79 cases satisfying the case definition occurred in the present outbreak and serum samples were collected from 7 patients for detection of VZV IgM antibodies by ELISA. Out of the total samples tested, five samples showed positive serology for VZV IgM. This confirmed the outbreak of Chickenpox in the KGBV, Chakulia. Conclusions: There is a desperate need of strengthening surveillance mechanism and field workers should be motivated for reporting cases timely so that the transmission of any viral exanthem may be checked at the earliest by application of control measures.